Small firms and the failure of national skills policies: adopting an institutional perspective. (March 2015) - Bishop, Dan
<x xml:space="preserve">Abstract</x> Both skills and small firms have been increasingly prominent in policy agendas across the world in recent years. Skills are now seen as being crucial to economic prosperity, yet evidence consistently shows much lower levels of training, on average, in small firms than in larger businesses. Policy makers in various countries have sought to address this perceived problem and to stimulate skills development in small firms, but have attempted to do so in different ways and with varying degrees of success. It is this divergence in national skills policies, as well as its causes and implications for skill formation in small firms, that this paper seeks to illuminate. In doing so, it adopts an 'institutional' perspective that advances current understanding of how and why skills policies adopted in different countries appear to have varying effects on small firms. Through employing this institutional analysis, the paper promotes an awareness of how historical, social and economic forces in the 'corporatist' systems, found for example in Germany and Scandinavia, tend to provide a more supportive context for skills development in small firms than the liberal free market systems found elsewhere in the world, such as in the USA, Canada and the UK – which is highlighted as an illustrative case in this paper.